Assessing Soil Degradation in Relation to Metal Pollution – A Multivariate Approach. Issue 7 (3rd October 2019) - Golui, Debasis; Datta, S.P.; Dwivedi, B.S.; Meena, M.C.; Varghese, E.; Sanyal, S.K.; Ray, P.; Shukla, A.K.; Trivedi, V.K.
ABSTRACT: Soil degradation due to elevated levels of metals is considered as a potent threat to soil quality and human health. Present investigation was carried out to develop a protocol for assessing degree of soil degradation in relation to metal accumulation due to long-term use of waste water and municipal solid-waste. For this purpose, surface soil samples having a long-history of receiving industrial-effluents, sewage, polluted river-water and municipal solid-waste were collected. Computation of conventional metal accumulation indices indicated metal-specific differential soil pollution at different sites. Multivariate analysis considering important physicochemical properties and ethylenediamine triacetic acid (EDTA)-extractable metal content of soil revealed more comprehensive status of soil-degradation due to metal accumulation. Results indicated that soils irrigated with cycle-factory effluent (soil quality index, SQI 0.42) were the most degraded and soils irrigated with polluted river-water (SQI 0.94) were the least degraded due to metal pollution. Hierarchical clustering suggests that quality of tube-well, river and sewage-effluent irrigated soils are almost similar, which differs significantly from other soils receiving industrial-effluents and solid-waste.